2022
DOI: 10.1021/acsapm.1c01876
|View full text |Cite
|
Sign up to set email alerts
|

Curing Behavior and Mechanical Properties of Tetra-Functional Epoxy Reinforced with Polyethyleneimine-Functionalized MXene

Abstract: The aerospace industry has started shifting toward polymer composites, especially epoxy-based composites. Because epoxy is inherently brittle, it must be suitably reinforced to enhance its fracture properties and make it suitable for aerospace applications. In this regard, we studied surface-modified Ti 3 C 2 nanosheets as toughening agents for aerospace-grade epoxy composites. Ti 3 C 2 T x (T = O, OH, and F) nanosheets were synthesized by acid etching of the Ti 3 AlC 2 precursor and further functionalized wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…The increase in Δ H is due to the large number of hydroxyl groups of VEHBP that catalyze the epoxy-amine curing reaction. Such results suggested that VEHBP effectively catalyzed the curing reaction as a result of the autocatalytic properties of VEHBP with abundant hydroxyl groups . The FT-IR spectra of 5%VEHBP/DGEBA/4-AFD at 120 °C during curing are shown in Figure c,d and Figure S5.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…The increase in Δ H is due to the large number of hydroxyl groups of VEHBP that catalyze the epoxy-amine curing reaction. Such results suggested that VEHBP effectively catalyzed the curing reaction as a result of the autocatalytic properties of VEHBP with abundant hydroxyl groups . The FT-IR spectra of 5%VEHBP/DGEBA/4-AFD at 120 °C during curing are shown in Figure c,d and Figure S5.…”
Section: Resultsmentioning
confidence: 82%
“…Such results suggested that VEHBP effectively catalyzed the curing reaction as a result of the autocatalytic properties of VEHBP with abundant hydroxyl groups. 50 The FT-IR spectra of 5%VEHBP/DGEBA/4-AFD at 120 °C during curing are shown in Figure 1c,d and Figure S5. As the reaction proceeded, the characteristic peak at 914 cm −1 for the epoxy group significantly decreased and finally disappeared, indicating that the epoxy group was completely consumed at the end of curing.…”
Section: Degradation Of Dynamic Covalent Epoxymentioning
confidence: 99%
“…These properties make MXenes an appealing choice for improving mechanical, optical, and electromagnetic interference shielding , properties of polymer nanocomposites. Recently, studies on the properties of MXene-incorporated epoxy nanocomposites started to receive attention. , It has been shown that the incorporation of MXene nanoplatelets can improve mechanical properties, , thermal conductivity, , and electrical conductivity , of epoxy nanocomposites. For example, the thermal conductivity of epoxy resin was improved by 141.3% to 0.587 W/mk with 1.0 wt % Ti 3 C 2 MXene filler .…”
Section: Introductionmentioning
confidence: 99%
“…[15,16] As a result, in order to substantially promote such interfacial interaction strength, using the chemicals having highly reactive functional groups that can directly react with epoxies and/or hardeners to decorate nanofillers was the most widespread method. [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] In this respect, since a large number of chemical bonds were formed between nanofillers and epoxies, nanofillers could be facilely incorporated into epoxy matrices and the high-quality interphase was constructed in the vicinity of nanofillers, thus imparting more energy absorption/dissipation. Theoretically, Janus particles, characterized by the amphiphilic and asymmetric nature, [33,34] can synchronously achieve the high dispersion extent and the strong chemical linkage via modifying the organic segments (e. g., short carbon chains) on one side of nanofillers (especially for nanosheets) and the reactive functional groups on the other side, respectively.…”
Section: Introductionmentioning
confidence: 99%